Moral Hazard during the Housing Boom: Evidence from Private Mortgage Insurance. (21st May 2021) - Bhutta, Neil; Keys, Benjamin J
Abstract: We provide novel evidence of misaligned incentives fueling a portion of the 2000s mortgage boom. We document that private mortgage insurance (PMI) companies expanded insurance issuance on high-risk mortgages purchased by Fannie Mae and Freddie Mac at the tail end of the housing boom, without changing pricing and despite knowledge of heightened housing risk. The expansion of PMI facilitated an unprecedented increase in Fannie and Freddie's risky purchases, extending the mortgage boom into 2007 and precipitating their collapse. We argue that this unraveling reflects a general moral hazard problem in insurance, coupled with misaligned incentives in the government-backed mortgage market.